Epidemiology of Obesity and Diabetes and Their Cardiovascular Complications - Bhupathiraju, Shilpa N. (Circ Res, 2016)
Obesity and diabetes have reached epidemic proportions in the past few years. In 2011–2012, more than a third of the US population was obese. Although recent trend data indicate that the epidemic has “leveled off”, prevalence of abdominal obesity continues to rise, especially among adults. As seen for obesity, the past few decades have seen a doubling of the diabetes incidence with an increasing number of type 2 diabetes cases being diagnosed in children. Significant racial and ethnic disparities exist in the prevalence and trends of obesity and diabetes. In general, in both adults and children, non-Hispanic blacks and Mexican Americans appear to be at a high risk than their non-Hispanic white counterparts. Secular changes in agricultural policies, diet, food environment, physical activity, and sleep have all contributed to the upward trends in the “diabesity” epidemic. Despite marginal improvements in physical activity and the US diet, the food environment has changed drastically to an “obesogenic” one with increased portion sizes and limited access to healthy food choices especially for disadvantaged populations. Interventions that improve the food environment are critical as both obesity and diabetes raise the risk of cardiovascular disease by nearly two-fold. Among those with type 2 diabetes, significant sex differences occur in the risk of cardiovascular disease such that diabetes completely eliminates or attenuates the advantages of being female. Given the substantial burden of obesity and diabetes, future research efforts should adopt a translational approach to find sustainable and holistic solutions in preventing these costly diseases.